Impact of diabetes education and self-management on the quality of care for people with type 1 diabetes mellitus in the Middle East (the International Diabetes Mellitus Practices Study, IDMPS) - Gagliardino, Juan Jose (2019)
Aims: Self-management (self-monitoring of blood glucose, plus self-adjustment of insulin dose) is important in diabetes care, but its complexity presents a barrier to wider implementation, which hinders attainment and maintenance of glycemic targets. More evidence on self-management is needed to increase its implementation and improve metabolic outcomes. Methods: Data from 1316 participants with type 1 diabetes mellitus who were enrolled from Middle East countries into the International Diabetes Management Practices Study (IDMPS), a multinational observational survey, were analyzed to assess the impact of education on disease management and outcomes. Results: A majority (78%) of participants failed to achieve glycemic target (HbA1c < 7.0% [<53 mmol/mol]). Participants who had received diabetes education (59%) were more likely to practice self-management than those who had not (odds ratio [OR]: 2.51; 95% confidence interval [CI]: 1.7–3.69; p < 0.001), and those who practiced self-management were more likely to attain target HbA1c than those who did not (OR: 1.49; 95% CI: 1.06–2.09; p = 0.023).